Succinate Dehydrogenase-Deficient Gastrointestinal Stromal Tumor With SDHC Germline Mutation and Bilateral Renal and Neck Cysts. (May 2019) - Stanley, Kaitlin; Friehling, Erika; Davis, Amy; Ranganathan, Sarangarajan
Gastrointestinal stromal tumors (GISTs) are rare in children. Succinate dehydrogenase (SDH)-deficient GISTs are wild type and lack KIT proto-oncogene receptor tyrosine kinase and platelet-derived growth factor receptor A ( KIT or PDGFRA ) mutations. These tumors result from germline SDH mutations, somatic SDH mutations, or SDH epimutants. Germline mutations in SDH genes ( SDHA, SDHB, SDHC, or SDHD ) suggest Carney–Stratakis syndrome, a paraganglioma syndrome with predisposition for GIST. Negative immunohistochemistry for SDHB indicates dysfunction of the mitochondrial complex regardless of the subunit affected. We present an adolescent male with an SDH-deficient GIST and SDHC germline mutation who developed bilateral renal cysts and neck cysts, not previously described in children with this mutation. Germline testing is critical when SDH mutations are discovered due to treatment and surveillance implications. Further investigations are necessary to fully define the phenotypic expression of this mutation.